ASET DIGITAL SEBAGAI OBJEK WARIS: Telaah Yuridis dan Fikih terhadap Cryptocurrency di Indonesia - Huda, Afiful; M. Misbahul Amin (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2025)
The development of digital technology has given rise to new forms of wealth that are non-physical yet possess high economic value, one of which is cryptocurrency. This article aims to analyze the position of cryptocurrency as an inheritance object from the perspective of Indonesian positive law and Islamic inheritance jurisprudence (fiqh al-mawaris). Using a normative legal research method, this study employs legislative and conceptual approaches to examine applicable regulations as well as classical and contemporary fiqh literature. The findings indicate that, legally, cryptocurrency in Indonesia is recognized as a legitimate digital commodity that can be owned and traded, thus qualifying as inheritable property under civil law. Meanwhile, in Islamic jurisprudence, crypto can be considered mal mutaqawwim (legally valid wealth) that is permissible to inherit, provided it is obtained lawfully and has beneficial value. However, the inheritance process for crypto requires proper access management and documentation to ensure effective transfer to heirs. Therefore, there is a need for regulatory reinforcement and education in digital inheritance planning that aligns with both national legal principles and sharia provisions.